Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors